PIG-SQUEALS : TEKNIK PEKIK BABI DARI GENRE SLAMMING METAL - Andhika Rifki Megantoro (Institut Seni Indonesia Surakarta, 2019)
ABSTRACTÂ Pig-squeals is a vocal technique that produces a sharp screech resembling the sound of a pig in the Slamming Metal genre. The sound-produced articulation sounds vague, even sounds amateur, but in fact pig-squeals vocals require difficult pronunciation and breathing techniques. The vocals of the pig-squeals itself contains aesthetic elements such as (1) quality of the sound,Â (2)Â volume intensity, and (3)